A randomised, phase III trial of once-daily fluticasone furoate/vilanterol 100/25 μg versus once-daily vilanterol 25 μg to evaluate the contribution on lung function of fluticasone furoate in the combination in patients with COPD. (February 2017) - Siler, Thomas M.; Nagai, Atsushi; Scott-Wilson, Catherine A.; Midwinter, Dawn A.; Crim, Courtney
Abstract: Background: The contribution of fluticasone furoate (FF) on lung function in the FF/vilanterol (VI) 100/25 μg combination has been demonstrated numerically, but not statistically. Methods: This multicentre, randomised, double-blind, controlled trial (GlaxoSmithKline study number 200820; clinicaltrials.gov NCT02105974) enrolled ≥40-year-old patients with chronic obstructive pulmonary disease (COPD), a ≥10-pack-year smoking history, a post-bronchodilator forced expiratory volume in 1 s (FEV1 ) 30–70% of the predicted value, a FEV1 /forced vital capacity ratio of ≤0.70, ≥1 COPD exacerbation in the previous 12 months requiring corticosteroids, antibiotics and/or hospitalisation, and current COPD symptoms. Participants received FF/VI 100/25 μg or VI 25 μg once daily. The primary endpoint was the change from baseline in trough FEV1 at day 84. Findings: 1620 patients were randomised and received at least one dose of FF/VI 100/25 μg (n = 806) or VI 25 μg (n = 814). At day 84, the FF/VI 100/25 μg group showed an adjusted mean treatment difference of 34 mL over VI 25 μg in change from baseline trough FEV1 (95% confidence interval [CI] 14–55; p = 0.001). There was no significant difference between the groups in the percentage of rescue medication-free 24-h periods. The FF/VI 100/25 μg group demonstrated a 42% risk reduction compared with the VI 25 μg group in time to first moderate/severe COPD exacerbation (95% CI 22–57; nominal p < 0.001). The incidence of on-treatment adverse events was similar between the groups. Interpretation: The contribution of FF in the FF/VI 100/25 μg combination on lung function in COPD was statistically significant. Funding: GlaxoSmithKline.